2022
DOI: 10.1186/s13287-022-03121-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of conditioned medium obtained from deferoxamine preconditioned umbilical cord mesenchymal stem cells on diabetic nephropathy model

Abstract: Background The therapeutic potential of mesenchymal stem cells (MSCs)-derived conditioned media (CM) can be increased after preconditioning with various chemical agents. The aim of this study is comparative evaluation of effects of N-CM and DFS-CM which are collected from normal (N) and deferoxamine (DFS) preconditioned umbilical cord-derived MSCs on rat diabetic nephropathy (DN) model. Methods After incubation of the MSCs in serum-free medium with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Finally, we demonstrated the isolated cells’ adipogenic and osteogenic differentiation abilities. Thus, by choosing two of the three primary tissues of mesoderm origin, we showed that our cells have MSC characteristics, in line with the studies in the literature [ 29 , 33 – 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…Finally, we demonstrated the isolated cells’ adipogenic and osteogenic differentiation abilities. Thus, by choosing two of the three primary tissues of mesoderm origin, we showed that our cells have MSC characteristics, in line with the studies in the literature [ 29 , 33 – 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…[41,47,59] MSCs also secrete growth factors such as vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), epidermal growth factor (EGF), stromal cell-derived factor-1 (SDF-1), insulin-like growth factor I (IGF-1), hepatocyte growth factor (HGF), fibroblast growth factor (FGF), [60][61][62][63] neural growth factor (NGF), glial cell-derived neurotrophic factor (GDNF), and brain-derived neurotrophic factor (BDNF). [64] Growth factors are essential effectors, providing therapeutic benefits like tissue repair, protection, fibrogenesis suppression, [65] and angiogenesis induction. [66] Furthermore, they have regulatory impacts on MSCs.…”
Section: Soluble Secretome Content Of Msc-cm: Cytokines Growth Factor...mentioning
confidence: 99%
“…[116] When the microvascular nature of the DN is considered, the glomeruli and tubular areas are expected to be primarily affected due to the presence of glomerular and peritubular capillaries, respectively. [117] In the glomerulus, the integrity of the glomerular filtration barrier (GFB), which is composed of podocytes along with fenestrated endothelium of capillaries and its basal lamina, is compromised under diabetic conditions, which in turn leads to a slow decline in renal function. [118] Currently, available treatments, including the application of anti-hypertensive drugs and sodium-glucose co-transporter 2 protein inhibitors, slow the progression of the disease.…”
Section: Nephropathymentioning
confidence: 99%
See 2 more Smart Citations